The Expressions of Sufi Literature and Its Development from the Islamic World to the Indonesian Archipelago - Angga Arifka (al-Afkar, Journal For Islamic Studies, 2026)
This article aims to analyze the historical development of Sufi literature from its roots in the Middle East to its spread to Indonesia, tracing the transformation of Sufi expression in various literary forms. Using a historical approach and descriptive qualitative method, this study traces the transformation of Sufi literature, which is not only a medium of spirituality, but also a tool for profound aesthetic expressions. Through a content analysis of these works, this article finds that poetry and literature can be means of Sufi expression regarding mystical experience. This article found that Sufi literature not only reflects the spiritual journey but also plays an important role in shaping literary traditions and religious thought in the Islamic world in general and in Indonesia in particular. Additionally, while each literary expression is intertextual, Sufistic literature shows its own uniqueness derived from Indonesian context.